Effectiveness of Probiotic, Prebiotic, and Synbiotic Supplementation to Improve Perinatal Mental Health in Mothers: A Systematic Review and Meta-Analysis - Desai, Vidhi; Kozyrskyj, Anita L.; Lau, Stuart; Sanni, Omolara; Dennett, Liz; Walter, Jens; Ospina, Maria B. (Frontiers in Psychiatry, 2021)
Introduction: There is an emerging interest in modulating the gut microbiota to target the gut-brain axis and improve maternal mental health in the perinatal period. This systematic review evaluated the effectiveness of prebiotics, probiotics, and synbiotics supplementation during pregnancy to reduce the risk of maternal mental health problems in the perinatal period. Methods: Electronic biomedical databases and clinical trial registries were searched from database inception through August 2020 to identify randomized controlled clinical trials (RCTs) evaluating the effect of probiotic, prebiotic, or synbiotic supplements administered to women during pregnancy on measures of perinatal depression, anxiety, and other mental health outcomes. Study selection, risk of bias appraisal, and data extraction were independently performed by two reviewers. Pooled mean differences (MD) and odds ratios (pOR) with 95% confidence intervals (CI) were calculated in random-effects meta-analyses for the outcomes of interest in the review. Results: From 3,868 studies identified through the search strategy, three RCTs of low risk of bias involving 713 participants were included, all three testing probiotics. There were no differences between probiotics and control groups in the mean depression scores (MD −0.46; 95% CI −2.16, 1.25) at end of follow-up. Although statistical significance was not achieved, probiotics showed an advantage in the proportion of participants scoring below an established cut-off for depression (pOR 0.68; 95% CI 0.43, 1.07). Compared to placebo, probiotics in pregnancy reduced anxiety symptoms (MD −0.99; 95% CI −1.80, −0.18); however, this advantage was not translated in a reduction in the proportion of participants scoring above an established cut-off for anxiety (pOR 0.65; 95% CI 0.23, 1.85). There were no differences between probiotics and control groups in global mental health scores at end of follow-up (MD 1.09; 95% CI −2.04, 4.22). Conclusion: There is limited but promising evidence about the effectiveness of probiotics during pregnancy to reduce anxiety symptoms and reduce the proportion of women scoring ABOVE a cut-off depression score. There is a lack of RCT evidence supporting prebiotics and synbiotics supplementation for similar purposes in the perinatal period. More research is needed before prebiotics, probiotics, and synbiotics are recommended to support maternal mental health and well-being in the perinatal period. Systematic Review Registration: PROSPERO, CRD42019137158.